Effect of Traverse Speed on the Defect Characteristic, Microstructure, and Mechanical Property of Friction Stir Welded T-Joints of Dissimilar Mg/Al Alloy - Sun Tao; Wu Siyu; Yifu Shen; Jin Jiayi; Lu Jiazhu; Qin Tianxiang (Advances in Materials Science and Engineering)
The AZ31 B/2024-T4 T-lap-joint was successfully fabricated by friction stir welding (FSW) with different welding parameters. The defect characteristics and metallurgical structure were observed and analyzed using optical microscope (OM) and scanning electron microscopy (SEM). Besides, the effects of defects and welding parameters on mechanical properties were investigated. The results show that an effective metallurgical reaction zone can be formed between Mg and Al (Mg-Al MRZ) and the island structures and lamellar structures appeared in the Mg-Al MRZ. The T-joints without tunnel defects can be obtained and the excellent mechanical properties of the T-joint were achieved using the welding speed of 50 mm/min. The tensile strength along the skin and the stringer was mainly affected by the kiss bonding defects.